2021
DOI: 10.1002/alz.12219
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the Cogstate Brief Battery for prevalent MCI and prodromal AD (MCI A+T+) in a population‐based sample

Abstract: Introduction This study evaluated the diagnostic accuracy of the Cogstate Brief Battery (CBB) for mild cognitive impairment (MCI) and prodromal Alzheimer's disease (AD) in a population‐based sample. Methods Participants included adults ages 50+ classified as cognitively unimpaired (CU, n = 2866) or MCI (n = 226), and a subset with amyloid (A) and tau (T) positron emission tomography who were AD biomarker negative (A–T–) or had prodromal AD (A+T+). Results Diagnostic accuracy of the Learning/Working Memory Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 42 publications
5
22
0
Order By: Relevance
“…The Remote Digital Memory Composite allowed to differentiate individuals with and without PACC5-based MCI-grade impairment with high diagnostic accuracy. This is higher or comparable to several other recently reported unsupervised (Mackin et al, 2018) or in-clinic and supervised digital cognitive assessments (Alden et al, 2021;Groppell et al, 2019;Kalafatis et al, 2021;Ye et al, 2020). Importantly, however, several earlier approaches reported outcomes by comparing MCI patients against samples that exclusively consisted of healthy asymptomatic older adults (Alden et al, 2021;Groppell et al, 2019;Kalafatis et al, 2021;Mackin et al, 2018;Maruff et al, 2013;Ye et al, 2020).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The Remote Digital Memory Composite allowed to differentiate individuals with and without PACC5-based MCI-grade impairment with high diagnostic accuracy. This is higher or comparable to several other recently reported unsupervised (Mackin et al, 2018) or in-clinic and supervised digital cognitive assessments (Alden et al, 2021;Groppell et al, 2019;Kalafatis et al, 2021;Ye et al, 2020). Importantly, however, several earlier approaches reported outcomes by comparing MCI patients against samples that exclusively consisted of healthy asymptomatic older adults (Alden et al, 2021;Groppell et al, 2019;Kalafatis et al, 2021;Mackin et al, 2018;Maruff et al, 2013;Ye et al, 2020).…”
Section: Discussionsupporting
confidence: 74%
“…This is higher or comparable to several other recently reported unsupervised (Mackin et al, 2018) or in-clinic and supervised digital cognitive assessments (Alden et al, 2021;Groppell et al, 2019;Kalafatis et al, 2021;Ye et al, 2020). Importantly, however, several earlier approaches reported outcomes by comparing MCI patients against samples that exclusively consisted of healthy asymptomatic older adults (Alden et al, 2021;Groppell et al, 2019;Kalafatis et al, 2021;Mackin et al, 2018;Maruff et al, 2013;Ye et al, 2020). In health care settings, the main challenge is to identify significant impairment within memory complainers.…”
Section: Discussionsupporting
confidence: 69%
“…While the standard OCL80 had been shown in many settings to be sensitive to changes in memory, recent studies applying this to characterize memory impairment in individuals classified clinically with mild cognitive impairment (MCI) or with biomarker positive status, showed lower than expected binary classification accuracy (though equivalent to delayed auditory verbal learning), did not discriminate between biomarker subgroups within cognitively unimpaired individuals and showed poor sensitivity using conventional cut-offs (22,23). Analysis of the outcomes from these studies suggested that the lower-than-expected sensitivity arose from a restriction in the range of the performance scores.…”
Section: Discussionmentioning
confidence: 99%
“…One important difference between decisions about cognitive change and cognitive impairment is that decisions about change are based on comparison of test performance withinindividuals over time, while decisions about cognitive impairment are based on comparison of an individual's performance to normative data ranges. Some studies using the OCL to classify impairment in AD show that its sensitivity is lower than expected for some classifications (22,23).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation